Proceedings of the International Conference on Psychological Studies (ICPSYCHE 2020) 2021
DOI: 10.2991/assehr.k.210423.016
|View full text |Cite
|
Sign up to set email alerts
|

Marital Distress and Satisfaction During the COVID-19 Pandemic: A Systematic Review

Abstract: COVID-19 pandemic brings tremendous impact on families, particularly on marital relationship. This paper reported findings on systematic review concerning the stressor and psychological problem encountered by married couples. We search in the Google Scholar database using the following keywords "marital satisfaction" and pandemic. We selected articles that met the inclusion criteria: original article, written in English, and fulltext available. From six articles that had been reviewed, we found out that either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Besides that, it can reduce the warmth of husband and wife relationships and decrease satisfaction and marital stability (Kerkman et al, 2000). The income status of both husband and wife can be a factor in achieving marital satisfaction and reducing stress within the family (Epifani et al, 2020). Therefore, family financial management is very important, especially with the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, it can reduce the warmth of husband and wife relationships and decrease satisfaction and marital stability (Kerkman et al, 2000). The income status of both husband and wife can be a factor in achieving marital satisfaction and reducing stress within the family (Epifani et al, 2020). Therefore, family financial management is very important, especially with the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Based on a recent systematic review, it was reported that the fear of COVID-19 influenced sexual relationships and intimacy and reduced marital satisfaction. 40 Turliuc and Candel reported that a combination of an external stressor like fear of COVID-19 with an internal stressor like socioeconomic status can lead to different responses regarding marital satisfaction. They reported that men and women responded differently during a crisis and that couples with lower socioeconomic status are more prone to greater stress and lower levels of marital satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it appears that domestic violence increased due to quarantine and spatial distancing during the COVID-19 outbreak 39. Based on a recent systematic review, it was reported that the fear of COVID-19 influenced sexual relationships and intimacy and reduced marital satisfaction 40. Turliuc and Candel reported that a combination of an external stressor like fear of COVID-19 with an internal stressor like socioeconomic status can lead to different responses regarding marital satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, economic difficulties and financial strain also harmed couple relationships by promoting greater dissatisfaction with marriage and lower relationship commitment, resulting in more frequent conflicts (see Epifani et al, 2021 for a review). For example, Balzarini et al (2020) showed how economic difficulties, perceived stress, and confining lockdown measures were negatively associated with the couple’s relationship quality.…”
Section: Introductionmentioning
confidence: 99%
“…The second aim is to explore the potential spillover effect from economic difficulties to women’s psychological maladjustment by considering the serial mediation of perceived stress and marital dissatisfaction. In other words, based on the literature ( Epifani et al, 2021 ; Friedline et al, 2021 ; Hertz-Palmor et al, 2021 ), we hypothesized that economic difficulties during the Covid-19 outbreak could predict the onset of higher levels of perceived stress which, in turn, negatively affects the couple’s relationship with consequences for psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%